Rural population at risk of development of diabetes mellitus: a cross sectional study using Indian Diabetic Risk Score in Bengaluru - K. R., Vidya; K., Lohit; P., Naveen Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Prevalence of diabetes mellitus is increasing in an alarming way throughout the world. More than 50% of the diabetic subjects in India remain unaware of their diabetes status and screening for risk factors of diabetes mellitus enable us to initiate appropriate control measures. This study was undertaken to identify the people who are at risk of diabetes mellitus in rural area of Bengaluru. Methods: It was a community based cross sectional study in which 1750 study subjects were randomly selected using multi stage random sampling method. Selected individuals were examined and interviewed using a semi structured questionnaire. Indian diabetic risk score was used to assess risk of developing diabetes. Data entry and analysis was done using SPSS version 20.0. Results: According to IDRS, 46.2% of respondents were in the moderate risk group and 33.1% were in the high risk group. Family history of diabetes, low physical activity and abdominal obesity were found to associate with high risk group. Conclusions: The prevalence of high risk for diabetes according to IRDS was 33%. Primordial and primary preventive actions are very much necessary.